1988
DOI: 10.1073/pnas.85.9.3125
|View full text |Cite
|
Sign up to set email alerts
|

Human thymic epithelial cells directly induce activation of autologous immature thymocytes.

Abstract: To study the role that epithelial cells of the thymic microenvironment play in promoting activation of immature CD7+, CD2+, CD4-, CD8-(double-negative) human thymocytes, we have isolated thymocyte subsets from normal postnatal thymus and have cocultured autologous double-negative thymocytes with pure populations of thymic epithelial (TE) cells. We report that TE cells directly activate double-negative thymocytes to proliferate and that TE cells enhance the ability of double-negative thymocytes to proliferate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…Since it has been demonstrated that bone marrow-derived hematopoietic precursors circulate in peripheral blood, it is conceivable that human epidermis that produces (at least) IL-1, GM-CSF, and IL-6/BSF-2 may serve to induce local differentiation of these cells. Some evidence suggests that certain T cell lymphomas, leukemias, and cell lines, as well as a subpopulation of double negative thymocytes, can respond to GM-CSF (22,30,31). That epithelial tissues, including skin and thymus, produce GM-CSF, IL-1, and thymic hormones (32,33) may relate to the differentiation of T cells in these tissues from bone marrow-derived precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been demonstrated that bone marrow-derived hematopoietic precursors circulate in peripheral blood, it is conceivable that human epidermis that produces (at least) IL-1, GM-CSF, and IL-6/BSF-2 may serve to induce local differentiation of these cells. Some evidence suggests that certain T cell lymphomas, leukemias, and cell lines, as well as a subpopulation of double negative thymocytes, can respond to GM-CSF (22,30,31). That epithelial tissues, including skin and thymus, produce GM-CSF, IL-1, and thymic hormones (32,33) may relate to the differentiation of T cells in these tissues from bone marrow-derived precursors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular signals between fetal liver (bone marrow) immigrants and thymic stromal cells that govern the activation process are as yet obscure. Recent evidence indicated that thymocyte differentiation requires interactions with more than one kind of stromal cell (52,53).…”
Section: Functional Expression Of Key Enhancer Element Factors Inmentioning
confidence: 99%
“…Purified thymocytes were teased from thymus tissue obtained from 5 control subjects (all younger than 7 years of age) during cardiovascular surgery and were purified as described previously (21). Fresh normal and activated peripheral blood mononuclear cells (PBMC) were prepared as previously described (22).…”
Section: Methodsmentioning
confidence: 99%
“…Activated T lymphocytes were prepared by activation of PBMC with the mitogen concanavalin A (Con A; 50 pg/ml for 3 days), washed in 0.3M a-methylmannoside (Sigma) to remove residual Con A, and then kept at 4°C prior to use in synovial cell-T cell binding assays (22). In some experiments, synovial lymphocytes were isolated from synovial tissue or fluid by mechanical disruption of tissue and Ficoll-Hypaque density centrifugation (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation